Sundanese "kitāb" printed in early-twentieth-century Egypt as evidence of Islamic transregional networks - Rohmana, Jajang A. (Wacana, Journal of the Humanities of Indonesia, 2025)
This article will focus on Sundanese literacy as observed in the Islamic transregional networks established between the Middle East and West Java in the early twentieth century. Sundanese kitāb printed in Egypt by three Sundanese ulama reflect an increasingly intensive use of the Sundanese language in Islamic teaching in West Java compared to the earlier predominant use of Javanese. There is also a shift on the part of Sundanese ulama from manuscript to print culture. This shift corresponds to the increasing number of pilgrims and Malay-Indonesian students, including those from West Java, in Mecca and the consequent increasing demand for books. This demand was met by publishers who made use of the new print technology and the Jāwī ulama in the Middle East asked publishing assistance from Egyptian publishers. This accelerated the spread of Islamic knowledge encouraging Islamization at a time when rapid modernization was also occurring.